PENERAPAN DOUBLE EXPONENTIAL SMOOTHING UNTUK MEMPREDIKSI JUMLAH PENERIMAAN MAHASISWA BARU - Ena, Maktisen; Adrianingsih, Narita Y.; Malese, Maryanes A. (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research aims to find out or predict the number of new students who will register for admission at the UNTRIB Kalabahi campus in 2024. The data collection technique used in this research is secondary data obtained from BAAK (Student Academic Administration Bureau) UNTRIB Kalabahi from 2007 until 2023 there are 17 data. The method used in this research is the Double Exponential Smoothing method from Brown to analyze the number of new students in 2024 based on new student data in 2007-2023 by testing using 9 alpha value parameters, namely 0.1 to 0.9 by looking at the Mean value The smallest Absolute Percentage Error (MAPE). The research results show that the smallest MAPE value is 6.35% with an alpha parameter value of 0.5. The estimated number of new student admissions in the 2024/2025 academic year is 590 people